Molecular characterization of Malaysian marine fish species using partial sequence of Mitochondrial DNA 12S and 16S rRNA Markers - Siti Farah Quraishia,; Sundararajulu Panneerchelvam,; Zafarina Zainuddin,; Nur Haslindawaty Abd Rashid, (Universiti Kebangsaan Malaysia, 2015)
This study was conducted to characterize the selected marine fish species using partial sequence of mtDNA 12S and 16S rRNA gene. PCR amplification of 12S and 16S rRNA generated PCR amplicons at 350 and 440 bp lengths, respectively. Sequence analysis was performed using BioEdit software. Phylogenetic tree was constructed using MEGA software. Two reference species have been used namely Gobio gobio (AB239596 and EF112528) and Pentapodus caninus (DQ533268 and DQ532933). Based on the result obtained, mtDNA 12S and 16S rRNA were found to be useful as molecular markers for fish species identification. These markers will provide correct identification of fish species when considered along with morphological characteristics.